Perancangan Kapasitas Produksi Produk Electronic Control Unit (Ecu) - Oktavia Sunny; Anastasia Lidya Maukar; Ineu Widaningsih Sosodoro (JIE Scientific Journal on Research and Application of Industrial System, 2019)
The export demand for Electoric Control Unit (ECU) products, which continued to increase by approximately 25% in December 2014, made the company have to review its production capacity. Based on current production capacity data, it is known that the process cycle time is 64.9 seconds while the takt time needed to meet consumer demand is 39.4 seconds for the first production line. With working time included in working hours overtime, this first-line capacity cannot meet production demands. Work measurement is done to get actual time data for capacity calculation. Man machine chart is one of the tools used to determine the production line capacity with the current number of machines and workers. To be able to fulfill the production demand, a capacity design with 2 proposed improvements is carried out, namely: adding a working time of one shift for the first production line or balancing work time between lines. By calculating the results obtained and the costs incurred, the proposal for balancing work time between lines becomes more effective to do.